How OECD countries subsidize oil and natural gas producers and modeling the consequences: A review. (April 2019) - Zhao, Xu; Dahl, Carol A.; Luo, Dongkun
Abstract: Since fossil fuel subsidies entail significant economic, fiscal, social and environmental costs, more and more attention is being paid to phasing out fossil fuel subsidies. The OECD has recently completed a report quantifying the amount of both producer and consumer subsidies for their member countries, and some work has been implemented on analyzing the effects of consumer subsidy removal. However, there is hardly any investigation of the consequences of producer subsidies. In this paper, we focus on oil and gas producer subsidies of OECD countries and their effects. First, we describe the transfer mechanisms indicated by the OECD report for producer subsidies. In order to recommend models to analyze the influence of removing producer subsidies, we review upstream oil and gas models and provide a taxonomy for them. From them we recommend the most appropriate models for each type of producer subsidy to model upstream decision making. Our contribution in this paper is to categorize the upstream models we have found, compare their main features, as well as recommending best in class models for analyzing the effects of each type of upstream producer subsidy. Highlights: Reviewed and categorized upstream oil and gas optimization and econometric models. Reviewed and categorized upstream oil and gas process and bottom-up models. Categorized the producer subsidies and their transfer paths. Recommended models for analyzing the effects of phasing out producer subsidies.